AS INTERAÇÕES ENTRE ORAÇÃO E MAGIA NO CRISTIANISMO PRIMITIVO NA CARTA DE TIAGO 5.12-20 - SILVA, Renato Cunha (2018)
The interactions of the Early Christianity can be observed in the texts from New Testament as well in other variety of texts from Early Christianity which are comprised of apocrypha and pseudepigraphs texts. Christianity has its origin in the Judaism, so it interacts directly with the Judaic culture, rituals, magic and social practices. Additionally to that, the Christianity was in a Hellenized world that brought some acculturation. In this miscellaneous scenario the letter of James was written and from it these interactions can be observed. In James 5.12-20 it is possible to notice magic/miracle, here a prayer was registered as what could be an interaction of prayer and magic. Our research proposes to identify the characteristics between prayer and magic and its possibility to have influenced this text narrative. Moreover, we also intend to demonstrate the similarities between James 5.12-20 and the Judaic literature from Greek Magic Papyrus, which compose the cultural context where Early Christianity is inserted, and its possible interactions. Also, comparisons between the mage and the presbyter will be made, about the miracle worker/mage made into a presbyter.